Novel, genetically induced mouse model that recapitulates the histological morphology and immunosuppressive tumor microenvironment of metastatic peritoneal carcinomatosis. Issue 1 (27th February 2020) - Tseng, Ssu-Hsueh; Park, Sung-Taek; Lam, Brandon; Tsai, Ya-Chea; Cheng, Max A; Farmer, Emily; Xing, Deyin; Hung, Chien-Fu
Abstract : Background: Peritoneal carcinomatosis is a hallmark of advanced peritoneal tumor progression, particularly for tubal/ovarian high-grade serous carcinomas (HGSCs). Patients with peritoneal carcinomatosis have poor survival rates and are difficult to treat clinically due to widespread tumor dissemination in the peritoneal cavity. Methods: We developed a clinically relevant, genetically induced, peritoneal carcinomatosis model that recapitulates the histological morphology and immunosuppressive state of the tumor microenvironment of metastatic peritoneal HGSCs by intraperitoneally injecting shp53, AKT, c-Myc, luciferase and sleeping beauty transposase, followed by electroporation (EP) in the peritoneal cavity of immunocompetent mice (intraperitoneal (IP)/EP mice). Results: Similar to the spread of human ovarian cancers, IP/EP mice displayed multiple tumor nodules attached to the surface of the abdomen. Histopathological analysis indicated that these tumors were epithelial in origin. These IP/EP mice also displayed a loss of CD3 + T cell infiltration in tumors, highly expressed inhibitory checkpoint molecules in tumor-infiltrating and global CD4 + and CD8 + T cells, and increased levels of transforming growth factor-β in the ascites, all of which contribute to the promotion of tumor growth. Conclusions: Overall, our tumor model recapitulates clinical peritoneal HGSC metastasis, which makes it ideal for preclinical drug screening, testing of immunotherapy-based therapeutics and studying of the tumor biology of peritoneal carcinomatosis.